(untitled) (Research, Society and Development, 2021)
It will approach the juridical status of non-human animals in the Brazilian legal order, further the sentience of the non-human animal, as well as your place in the family environment using the contemporary concept of multispecies family, in which we understand the non-human animals as a member of the family. The fact of the non-human animals being considering as legal subjects by their multispecies family justify the plea for the shared custody in the marital dissolution moment. But even if they are scientifically and socially declared sentients. There isn’t a law to protect them inside the family environment. So, the judiciary cumulate different comprehensions to threat the pet’s shared custody right: sometimes it uses the analogy and considers them a legal subject and sometimes it does as the law says, according to article 82 of the Civil Code it threats them as objects. Therefore, while it doesn’t exist a law giving the non-human animals an appropriate status which assure their rights, it’s probable that there won’t be a pacific understanding as far as the pet’s shared custody is concern.